O Estado Nacional de Competência: expropriação e concentração - a Refinaria Bicentenario de Atitalaquia-Tula, Hidalgo, México - Gómez, Luis Alberto Luna [UNESP] (Universidade Estadual Paulista (Unesp), 2017)
Esta pesquisa enfoca as transformações na região de Hidalgo, México, causadas pelo projeto da refinaria Bicentenario concebido em 2008, na região de Atitalaquia e Tula. As transformações espaciais foram derivadas de um projeto governamental, cuja especulação baseada na indústria e serviços sobre a desvalorização da terra, a fim de ganhar o máximo de lucro expropriando os camponeses. Nessa ação de diferentes atores sociais estão relacionados os agricultores da região, Petróleos Mexicanos (Pemex), o Sindicato dos Trabalhadores do Petróleo da República Mexicana (STPRM), a União Nacional dos Trabalhadores e Empregados Felipe Carrillo Puerto, o Governo Federal, também os governos estadual e municipal, e a ICA, a empresa imobiliária que ganhou licitação para fazer o projeto. Esses gestores realizaram seus propósitos em fases posteriores de acumulação que se enquadram, espacial e temporalmente no Estado Nacional de Competência (ENC). Essa política promoveu a sazonalidade do capital financeiro dentro de suas fronteiras, com base na política de posicionamento. Por esta razão, o quadro teórico e metodológico para esta pesquisa foi fornecido pela geografia crítica, observando a acumulação baseado no confronto das relações sociais e interesses do modo de produção capitalista neoliberal. O mapeamento do espaço e dados econômicos, sociais e ambientais, tais como valores de uso da terra, foram consultados os dados do Instituto Nacional de Estatística, Geografia e Informática (Inegi) e do Conselho Nacional de População (Conapo), fontes de dados prioritários, com destaque para o Marco Geoestadístico Municipal de 2010: Recenseamento da População e Habitação (2010), Censo Econômico e do Censo Agropecuário. É importante definir alguns conceitos que serão essenciais para a análise: por "Estado Nacional de Competência", se entende a formação histórica das relações estabelecidas em diferentes escalas dentro do México, que estão sendo divididas em dois pontos – políticas públicas e planos econômicos que tornam vulneráveis a produção camponesa e institui a flexibilização das relações de trabalho. Isso favoreceu economicamente grupos econômicos através de processos desregulamentação e da oferta de baixos valores do solo mexicano, causando distorções regionais profundas. E também a política de posicionamento, estratégia preparada pelo Estado Nacional de Competência para atrair capital financeiro nacional e internacional para que possa investir nos setores produtivos, sendo não só promotor, mas também receptor dos lucros advindos desses investimentos.

This research focuses on the spatial transformations caused by the Bicentennial refinery project conceived in 2008, in the region of Atitalaquia and Tula, Hidalgo, Mexico. The spatial transformations were derived from space conceived from the representation and juxtapose speculation based on industry and services on the devaluation of the rent of land, in order to earn maximum profit. In this action different stakeholders are related, such as farmers in the region, Pemex, the Union of Petroleum Workers (STPRM), the National Union of Workers and Employees Felipe Carrillo Puerto, the Federal Government relate, state governments and municipal, and ICA, the real estate company that won some tenders to be in charge of the project. These actors conduct their purposes consciously or unconsciously in subsequent phases of accumulation that fall, spatially and temporally in the National Competition State which seeks to promote the seasonality of finance capital within its borders, based on political positioning. For this reason, the theoretical and methodological framework applied to this research is provided by the critical geography, same applies for the deductive analysis of the phenomenon, noting the accumulation based on the perception and conception of the social relations zoning, a capitalist mode of production, consulting, so that the design of the mapping of space not only for the administrative levels of government, but stressed that allows modeling economic, social and environmental data, such as the values of the use of the land, for which the National Institute of no, Geography and Informatics and the National Population Council were sources of priority data, highlighting the Municipal Geostatistical Framework, 2010: Census of Population and Housing, Economic Census and the Agricultural Census. It is important to define some categories for the understanding of this research and that will be essential for analysis. By "National Competition State" means the historical formation of relationships established at different scales within Mexico, which are being split into two forms: political and economic, tending to favor the economic form through the process of deregulation and the supply use of the values of Mexican soil. In addition to the above concept is that of "political positioning", it is understood, the strategy prepared by the National State Competition to attract domestic and foreign financial capital for it to invest in production, being not only promoter but also a partner. Also, it should be explained that by representation, the concept refers to the phenomenon of social agents facing a something, such as the Bicentennial refinery, they become safe actors, though, is partly an illusion, that was guaranteed and supported by actions and resources, but was not materialized to the extent of leaving unused the land acquired for this purpose. It is a sign that represents something, turning into itself, producing actions, semi-illusory, and semi-real. Finally, for production of space is understood that the production of actions that actors perform on the Earth's surface, considering that the idea of observing the space as a God-given place has already been left behind. Thus, the term of production emphasizes social action to transform reality.
The National State of Competence: expropriation and concentration. The Bicentenario Refinery of Atitalaquia-Tula, Hidalgo, Mexico
Keywords: Expropriação; Refinaria bicentenario; Política de posicionamento; Estado nacional de competência; México; Expropriation; Bicentenario refinery; Positioning policy; National state of competence; Mexico